Lignin and biodegradable polymer blends with chemically treated biofiller for green thermoplastic composites - Waleed Y. Rizg; Amerh Aiad Alahmadi; Mohammed Baradwan; Rahul Dev Bairwan; Marwan M; Ahmed K. Mohamed; Sherif El Saadany; CK Abdullah; H.P.S. Abdul Khalil (eXPRESS Polymer Letters)
This study investigated the development of thermoplastic composites by incorporating crude lignin extracted from coir fiber waste, into poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), a biodegradable polymer. The extracted crude lignin was blended with PHBV as a matrix, and spent coffee grounds (SCG) were used as biofillers. SCG were chemically modified through sodium hydroxide (NaOH) treatment and maleic anhydride (MA) grafting to enhance their compatibility with the PHBV/lignin blend. Raw and modified SCG were characterized for their functional, morphological, and thermal properties before being incorporated. Thermoplastic biocomposites were prepared via melt compounding and compression molding and evaluated for water barrier, morphological, mechanical, and thermal properties. Results showed that MA-grafted SCG significantly enhanced PHBV-lignin properties, increasing tensile strength by 23.7% and thermal stability by 11.9% compared to the control matrix. Optimal performance was observed at 5% MA-grafted SCG filler loading. However, higher SCG concentrations (7%) led to filler agglomeration, negatively affecting the material properties. This research demonstrated the potential of utilizing agricultural and food waste to create high-performance thermoplastic composites for future applications in biodegradable packaging, contributing to the advancement of a circular economy and environmental sustainability.